2022
DOI: 10.1002/lio2.732
|View full text |Cite
|
Sign up to set email alerts
|

Voice emotion recognition by Mandarin‐speaking pediatric cochlear implant users in Taiwan

Abstract: Objectives: To explore the effects of obligatory lexical tone learning on speech emotion recognition and the cross-culture differences between United States and Taiwan for speech emotion understanding in children with cochlear implant.Methods: This cohort study enrolled 60 cochlear-implanted (cCI) Mandarin-speaking, school-aged children who underwent cochlear implantation before 5 years of age and 53 normal-hearing children (cNH) in Taiwan. The emotion recognition and the sensitivity of fundamental frequency (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
3
10
1
Order By: Relevance
“…While previous studies have shown developmental effects as well as sensitivity to talkers and emotions in children with CIs emotional prosody perception (Volkova et al 2013;Wang et al 2019;Barrett et al 2020;Lin et al 2022), the interactive effects between age, cognitive status, emotion categories, and talker have not been studied. The present study builds on previous findings by investigating these interactions.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…While previous studies have shown developmental effects as well as sensitivity to talkers and emotions in children with CIs emotional prosody perception (Volkova et al 2013;Wang et al 2019;Barrett et al 2020;Lin et al 2022), the interactive effects between age, cognitive status, emotion categories, and talker have not been studied. The present study builds on previous findings by investigating these interactions.…”
Section: Introductionmentioning
confidence: 97%
“…This suggests that concepts of different emotions (termed emotion understanding) are developed by the time children with CIs are school age. However, school-age children with CIs still show significant deficits relative to children with normal hearing in vocal emotion recognition tasks (Luo et al 2007;Chatterjee et al 2015;Gilbers et al 2015;Barrett et al 2020;Lin et al 2022). Strong intersubject variability is also evident in performance by children with CIs in vocal emotion identification accuracy, with some of them achieving excellent performance while others' scores are at chance level (Chatterjee et al 2015;Barrett et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the properties of electrode-nerve interface, the transmitted information is reduced in spectrotemporal details (for an overview see Başkent et al, 2016). In particular, the perception of vocal and musical emotion is consistently reported to be challenging for CI users (Ambert-Dahan et al, 2015; Chatterjee et al, 2015, 2023; Lin et al, 2022; Luo et al, 2007; Paquette et al, 2018; Volkova et al, 2013). The ability to perceive vocal emotions in CI users has been shown to be linked to voice cue discrimination thresholds for emotion-related acoustic features such as the voice cues of voice pitch (related to voice fundamental frequency, F0) (Barrett et al, 2020; Deroche et al, 2016; Lin et al, 2022) and vocal tract length (VTL; related to formants, Chuenwattanapranithi et al, 2008; Nussbaum et al, 2022; von Eiff et al, 2022) as well as to listeners’ ratings of quality of life (QoL) (Luo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Perception of prosody of speech is very important in speech understanding. Prosody has linguistic function (e.g., in lexical tones or intonation), expressive function (in semantic, attitudinal, psychological, and social domains), [18,23,24] and plays an important role in expediting spoken language development. [25][26][27] Mandarin and English are the 2 widely-spoken languages in the present time.…”
Section: Introductionmentioning
confidence: 99%